The business idea: problems of readiness and abandonment as a prerequisite to scenario thinking and planning. - Anderson, Paul (Curtin University, 1999)
Documenting organisational history and heritage, it is argued, is an increasingly critical precursor to effective corporate and scenario planning. This study proposes that organisational history and heritage can be encapsulated in any local setting through the application of van der Heijden's (1996) conceptual framework i.e. the "business" idea. The study demonstrates that documenting the organisational business idea in use is a valid and meaningful planning activity. Secondly, the possession of multiple perspectives on the business idea in use, means that current and future planning teams will collectively be better informed, more competent and ready to abandon established ways of doing business and to strategise about unknown futures.Interpretivist methodology utilising an embedded single case study method was applied to an organisation undergoing change: the Family Planning Association of Western Australia, Inc. (FPWA). A stratified sample of thirty-four members from FPWA's institutional (Board of Management), corporate, organisational (service managers and coordinators) and technical (service delivery) organisational levels were interviewed, with the intent of capturing broad perceptions from each organisational level of the derived categories of the business idea framework. The categories investigated were those of organisational purpose, customer value created, distinctive competencies, competitive advantage, organisational uniqueness, positive and negative forces, and results. The study sought evidence to support each of the derived categories, as well as looking to elaborate on the process and task of business idea investigation and articulation.Interview outcomes were transcribed, coded and analysed using NUD*IST, the intent being to craft a consolidated model of the business idea in use at FPWA. Multiple perspectives from the four nominated organisational levels were isolated by copying the core NUD*IST database four times. A copy was assigned to each organisational group wherein interviews belonging to the assigned group were retained, and the remainder deleted, thereby allowing the differences between each group to emerge. Elements of the NUD*IST index system for the core and four derived databases were then exported to Decision Explorer for graphical representation and gap analysis. Narrative analysis was applied to relate the study's findings.Key internal and external factors were identified as both driving and hindering evolution of FPWA's corporate culture. It was in these areas that key insights to the meta value of the study emerged. The key driving external force was the changing face of sexual health community issues, specifically the expansion of services beyond women's health to cover men's, gay, lesbian and special need groups-FPWA is about sex (positive external force).The question of who should pay for sexual health services is also challenged. Concerns over the withdrawal of government funding (negative external force) and a lack of perceived direction (negative internal force) by members at the organisational and technical levels, has led to behaviour aimed at corporate survival and maintenance of the status quo. Many staff at FPWA were interpreted as clinging tightly to social justice, women's rights issues, reflecting the humanitarian (positive internal force) value-based aspects that have sustained FPWA's service over its twenty-five years of service.The conceptual framework associated with the business idea proved to be essentially a system that maps the organisation's corporate and commercial rationale. The systemic insights that emerged from the study at FPWA enabled the researcher to build a four level hierarchical model of systemic appreciation with van der Heijden's framework as the foundation. Issues of corporate age and stage of growth, systemic archetype and the key question facing the scenario planning team made up the higher levels of an emergent model of scenario planning readiness. The critical thinking associated with documenting the organisational history and heritage in the form of the business idea system has therefore generated a crucial link in the corporate and scenario planning process: the articulation of the key question as a catalyst to the next stage of corporate strategy formulation.